2016
DOI: 10.1016/j.neuroimage.2015.08.069
|View full text |Cite
|
Sign up to set email alerts
|

Local inhibitory plasticity tunes macroscopic brain dynamics and allows the emergence of functional brain networks

Abstract: Rich, spontaneous brain activity has been observed across a range of different temporal and spatial scales. These dynamics are thought to be important for efficient neural functioning. A range of experimental evidence suggests that these neural dynamics are maintained across a variety of different cognitive states, in response to alterations of the environment and to changes in brain configuration (e.g., across individuals, development and in many neurological disorders). This suggests that the brain has evolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
160
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(173 citation statements)
references
References 63 publications
13
160
0
Order By: Relevance
“…The relationship between brain dynamics and cognitive function is complex and likely depends on both brain state and cognitive domain. With respect to state, our findings are in line with a previous study showing low levels of dFC, but high levels of sFC, during task engagement, whereas at rest the brain displayed an opposite pattern (Hellyer et al., ). Furthermore, it could be hypothesized that certain cognitive domains benefit more from high levels of dFC than others.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The relationship between brain dynamics and cognitive function is complex and likely depends on both brain state and cognitive domain. With respect to state, our findings are in line with a previous study showing low levels of dFC, but high levels of sFC, during task engagement, whereas at rest the brain displayed an opposite pattern (Hellyer et al., ). Furthermore, it could be hypothesized that certain cognitive domains benefit more from high levels of dFC than others.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies indicate that the dynamics of FC (dFC) are indeed related to cognitive function in healthy subjects and certain patient populations (Cole et al, 2013;Douw, Wakeman, Tanaka, Liu, & Stufflebeam, 2016;Douw et al, 2015;Hellyer, Jachs, Clopath, & Leech, 2016;Nguyen et al, 2016), and that dFC may supersede traditional neuroimaging measures in explaining cognitive variance (Douw et al, 2015(Douw et al, , 2016Jia, Hu, & Deshpande, 2014;Nguyen et al, 2016). This body of literature is heterogeneous, but suggests that the relationship between dFC and cognition depends on the combination of the brain state in which it is measured (at rest or during a task) and the cognitive domain investigated.…”
mentioning
confidence: 99%
“…This is consistent with a homeostatic neuroplasticity model of intelligence in which maintenance of an optimal small-world dynamic involves minimizing long distance information processing and maximizing the efficiency of local information processing29. Phase reset operates primarily in the local hub domain to recruit and allocate resources to efficiently process information while information flow operates in the long range compartments to compensate for inefficiencies in the local domain.…”
Section: Discussionsupporting
confidence: 78%
“…A strong link between cognitive flexibility and creative performance has been demonstrated in previous studies736. Recent studies have indicated that cognitive flexibility is highly associated with neural metastability162737. A greater dFC state transition frequency enables the brain regions of creative individuals to engage and disengage more flexibly without experiencing locked interactions.…”
Section: Discussionmentioning
confidence: 72%